2015
DOI: 10.1177/0284185115574737
|View full text |Cite
|
Sign up to set email alerts
|

Multi-detector CT and MRI of microembolized myocardial infarct: monitoring of left ventricular function, perfusion, and myocardial viability in a swine model

Abstract: MDCT can longitudinally quantify regional perfusion deficits, LV dysfunction, and resorption of microembolized MI. MDCT or MRI can be used alternatively after coronary interventions in cases of contraindications for one modality or the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Obtaining accurate baseline values is important for the application of new innovative techniques in both experimental and clinical studies [21]. The findings from the present study showed that the left ventricular end-systolic volume (LVESV) was lower, and the left ventricle ejection fraction (LVEF) and stroke volume (SV) were higher compared with the findings previously reported from studies that used early-generation DSCT [22,24]. However, the findings from the present study were similar to those described by Busch et al in 2008 in a study that compared dual-source CT with cardiac magnetic resonance imaging (MRI) [25].…”
Section: Discussionsupporting
confidence: 56%
“…Obtaining accurate baseline values is important for the application of new innovative techniques in both experimental and clinical studies [21]. The findings from the present study showed that the left ventricular end-systolic volume (LVESV) was lower, and the left ventricle ejection fraction (LVEF) and stroke volume (SV) were higher compared with the findings previously reported from studies that used early-generation DSCT [22,24]. However, the findings from the present study were similar to those described by Busch et al in 2008 in a study that compared dual-source CT with cardiac magnetic resonance imaging (MRI) [25].…”
Section: Discussionsupporting
confidence: 56%
“…61 Similar techniques are used in imaging (magnetic resonance imaging or computed tomography) studies to quantify LV function in animal models of HFrEF and compare microemboli with surgical interventions. 57,62,63 These protocols are more time-consuming as well as stressful to the animals, as multiple treatments must be performed in a short amount of time.…”
Section: Animal Models Of Hfrefmentioning
confidence: 99%
“…(20 %). This difference in the rate of infarct resorption can be affected by: (1) infarct size [7,27] and (2) the presence of MVO inhibits/delays infarct resorption [7,27,28]. The limitation of DE is poor sensitivity in defining peri infarcted zone [29] and small patchy microinfarct [25].…”
Section: Myocardial Viabilitymentioning
confidence: 99%